Relationship between inflammatory status and microbial composition in severe asthma and during exacerbation. Issue 11 (15th July 2022) - Diver, Sarah; Haldar, Koirobi; McDowell, Pamela Jane; Busby, John; Mistry, Vijay; Micieli, Claudia; Brown, Vanessa; Cox, Ciara; Yang, Freda; Borg, Catherine; Shrimanker, Rahul; Ramsheh, Mohammadali Yavari; et al.
Abstract: Background: In T2‐mediated severe asthma, biologic therapies, such as mepolizumab, are increasingly used to control disease. Current biomarkers can indicate adequate suppression of T2 inflammation, but it is unclear whether they provide information about airway microbial composition. We investigated the relationships between current T2 biomarkers and microbial profiles, characteristics associated with a Proteobacteria HIGH microbial profile and the effects of mepolizumab on airway ecology. Methods: Microbiota sequencing was performed on sputum samples obtained at stable and exacerbation state from 140 subjects with severe asthma participating in two clinical trials. Inflammatory subgroups were compared on the basis of biomarkers, including FeNO and sputum and blood eosinophils. Proteobacteria HIGH subjects were identified by Proteobacteria to Firmicutes ratio ≥0.485. Where paired sputum from stable visits was available, we compared microbial composition at baseline and following ≥12 weeks of mepolizumab. Results: Microbial composition was not related to inflammatory subgroup based on sputum or blood eosinophils. FeNO ≥50 ppb when stable and at exacerbation indicated a group with less dispersed microbial profiles characterised by high alpha‐diversity and low Proteobacteria. Proteobacteria HIGH subjects were neutrophilic and had a longer time from asthma diagnosis than Proteobacteria LOW subjects. In those studied, mepolizumab did not alter airway bacterial load or lead to increased Proteobacteria. Conclusion: High FeNO could indicate a subgroup of severe asthma less likely to benefit from antimicrobial strategies at exacerbation or in the context of poor control. Where FeNO is <50 ppb, biomarkers of microbial composition are required to identify those likely to respond to microbiome‐directed strategies. We found no evidence that mepolizumab alters airway microbial composition. Abstract : FeNO ≥50 ppb, when stable and at exacerbation, indicates a subgroup with an even microbial composition, with high alpha‐diversity measures and low relative abundance of Proteobacteria. Proteobacteria HIGH severe asthmatics are neutrophilic and have a longer duration of disease than those who are Proteobacteria LOW . In a small subset with paired data at baseline and ≥12 weeks, mepolizumab suppressed blood eosinophils but did not increase total airway bacterial load or lead to increased proportions of Proteobacteria.Abbreviations: FeNO, fractional exhaled nitric oxide; GINA, Global Initiative for Asthma; MEX, Exploring Asthma Exacerbations in Mepolizumab Treated Patients; ppb, parts per billion; RASP‐UK, A Pragmatic Trial of Corticosteroid Optimisation in Severe Asthma; rDNA, ribosomal DNA; seq, sequencing